2018
DOI: 10.3747/pdi.2017.00125
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Peritoneal Dialysis after Nonrenal Solid-Organ Transplantation

Abstract: Peritoneal dialysis appears to be an effective replacement therapy for patients with a previous history of solid-organ transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Two studies allowed direct comparisons of the rate of peritonitis in LT patients to that observed in cohorts of nontransplanted PD patients (see Table 3). 16,17,20 When pooling the reported experience from this systematic review, an overall peritonitis incidence rate of 1/34 patient-months was found, which represents 0.35 infections per patient-year. This rate is slightly higher than that recently reported for general PD population in Canada (0.27; 95% CI: [0.25, 0.30]) and Australia/New Zealand (0.29; 95% CI: [0.26, 0.32]) but similar to that observed in the United Kingdom (0.35; 95% CI: [0.30, 0.40]).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Two studies allowed direct comparisons of the rate of peritonitis in LT patients to that observed in cohorts of nontransplanted PD patients (see Table 3). 16,17,20 When pooling the reported experience from this systematic review, an overall peritonitis incidence rate of 1/34 patient-months was found, which represents 0.35 infections per patient-year. This rate is slightly higher than that recently reported for general PD population in Canada (0.27; 95% CI: [0.25, 0.30]) and Australia/New Zealand (0.29; 95% CI: [0.26, 0.32]) but similar to that observed in the United Kingdom (0.35; 95% CI: [0.30, 0.40]).…”
Section: Discussionmentioning
confidence: 93%
“…A total of 12 unique studies were deemed eligible for full-text screening 8 , 11 , 14 - 23 from which 4 presented quantitative results for at least 1 prespecified outcome. 15 , 16 , 20 , 21 The remaining studies were excluded based on reasons specified in Figure 1 . The studies by Shukla et al 22 and Cornelis et al 17 were excluded because cases reported were already described in the more recent publication by Saiprasertkit et al 20 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations